The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ef302024z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Structures of Molecules in Coal and Petroleum Asphaltenes by Using Mass Spectrometry

Abstract: Asphaltenes are a complex mixture of aromatic compounds that are present in petroleum and liquefied coal and have unknown molecular structures. Determination of the molecular structures of asphaltenes is greatly hindered by the extreme complexity of the mixtures. The average molecular weight of coal asphaltenes is known to be roughly half that of petroleum asphaltenes. In this study, tandem mass spectrometry experiments were used to compare the fragmentation patterns of molecular ions of the same mass-to-charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 20 publications
2
69
0
Order By: Relevance
“…25,[46][47] Based on the measured mass spectra, the apparent molecular weight distributions (MWD) were determined for six petroleum asphaltene samples originating from Bohai, Maya, Claire, Surmont, Montana and McKittrick. All of the studied asphaltenes from the American continent, Europe and China have similar apparent MWD, ranging from 200 up to 1400 Da.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…25,[46][47] Based on the measured mass spectra, the apparent molecular weight distributions (MWD) were determined for six petroleum asphaltene samples originating from Bohai, Maya, Claire, Surmont, Montana and McKittrick. All of the studied asphaltenes from the American continent, Europe and China have similar apparent MWD, ranging from 200 up to 1400 Da.…”
Section: Resultsmentioning
confidence: 99%
“…This is justified as we have previously demonstrated that the fragmentation patterns and main fragment ions of ionized asphaltenes are independent of the size of the isolation window as long as it is equal or less than 2 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Da. 25 The data were processed by using Thermo Xcalibur software. All measurements were repeated at least four times.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Collision-activated dissociation 38 Asphaltenes are a subset of molecules in crude oil whose 62 structural elucidation has proven difficult [1][2][3]. They comprise 63 the fraction of petroleum that is soluble in toluene but insoluble 64 in n-alkane [4] and can correspond to up to 20% of crude oil [5].…”
mentioning
confidence: 99%